Nutritional status of learners in schools with national school nutrition programme (NSNP) and the influence of school food environment on the food choices of learners in Mahwelereng Circuit, Mokopane, Waterberg District, Limpopo - Mahlakwane, Mokganyetje Tshephisho Audrey (2022)
Global Health: Human Nutrition